SOCIO-PSYCHOLOGICAL ASPECTS OF VIABILITY AS A COMPONENT OF THE PHENOMENA OF HUMAN CAPITAL AND LEADERSHIP IN THE CONTEXT OF AN INTERDISCIPLINARY APPROACH - D. Veselovskiy; L. Mosina (Вестник университета)
The de nition of human capital is given and its structure is considered. The de nitions of the components of human capital are given: viability, e ciency, ability to innovate, ability to learn. The components and characteristics of viability are determined. The importance of the ability to create and coordinate as a manifestation of the viability of the leader is substantiated. The components of the processes that the leader creates and coordinates in the organization are distinguished. The sources of the leader’s life forces are considered. The results of the research of satisfaction of four sources of vital forces of managers in the organization are given.